Evaluation of the "under-21 rule": Do young adult soccer players benefit? - Vaeyens, R.; Coutts, A.; Philippaerts, R. M. (Journal of Sports Sciences, 2005)
Young adult soccer players often encounter difficulty progressing from youth competition to being regularly selected for high-level, open-age competition. In an attempt to increase the playing opportunities of semi-professional and amateur under-21 players in first teams, the Royal Belgian Football Association required national division teams to include at least two players younger than 21 in their match selection (under-21 rule). Over four seasons, the following variables were analysed across 2138 semi-professional and amateur soccer players aged 16-39 years: (1) the number of times a player was selected to be in the first team squad; (2) the number of times a player was selected to play in the starting line-up; and (3) the number of minutes played. Chi-square analysis demonstrated that second and third division teams had complied with the new selection regulations. However, two-way analysis of variance of individual player data revealed no increase in the number of playing minutes in the under-21 group. It would appear that many teams had complied with the new regulations by selecting young players as substitutes. The results highlight the difficulties that talented young soccer players experience progressing from youth to senior competition. We conclude that the rule imposed by the Royal Belgian Football Association has failed to improve the playing opportunities of young adult soccer players. Alternative strategies for increasing playing opportunities for young talented players are required.